Pembuatan Sistem Kontrol Sliding Door untuk Rumah Tinggal - Sir Anderson - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
The sliding door is a type of door that works by sliding the door to the right or to the left. The sliding door is a type of door that is suitable for use in a room with small volume, because the sliding door does not require a large space. lack the sliding door when the door has been closed, lack the sliding door when the door has been closed, there still exists a gap between the open doors and walls so that air can be in and out freely. with the construction of the door using the hinge mechanism, can minimize these conditions. To make the sliding door works automatically, the authors make a set of control system that uses an analog system and the concept of open-loop control system. “dc motor” is used as drive for the door and “central lock actuator” as locking doors. On the control circuit voltage source used is equal to 12V. Control circuit components used are double circuit push button (NO and NC), 12V relay 8 feet, limits switches, motor DC of power windows, central lock actuator. The components were assembled for the purpose of changing the polarity of the DC motor is regulated by a relay mechanism. By changing the polarity of the dc motor, the motor can rotate to the left and to the right, so the door is connected to the motor would be moves to open and close according to the motor movement.